Proton‐Irradiation Effects on the Thermoelectric Properties of Flexible Bi2Te3/PEDOT:PSS Composite Films. (5th March 2019) - Goo, Giwon; Anoop, Gopinathan; Unithrattil, Sanjith; Kim, Wan Sik; Lee, Hye Jeong; Kim, Hyun Bin; Jung, Myung‐Hwan; Park, Jongjun; Ko, Heung Cho; Jo, Ji Young
Abstract: Bismuth telluride (Bi2 Te3 ) and poly(3, 4‐ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS) are two major inorganic and organic thermoelectric (TE) materials that are widely investigated for TE device applications. An inorganic–organic composite, based on Bi2 Te3 and PEDOT:PSS possessing a high TE figure of merit, has immense potential in fabricating highly efficient and flexible TE generators. In order to achieve an enhanced TE performance, the interdependent TE parameters such as electrical conductivity and Seebeck coefficient of the composite should be decoupled. In this study, the TE properties of the composites are enhanced through the creation of additional defects in Bi2 Te3 via proton irradiation. The structural variations occurred in Bi2 Te3 via proton irradiation are analyzed using X‐ray diffraction, X‐ray photoelectron spectroscopy, and transmission electron microscopy, which quantitatively reveal structural damages as well as deviations from the Bi2 Te3 stoichiometry. The proton irradiation‐induced antisite defects in the Bi2 Te3 crystal are found to be beneficial in decoupling the interdependent TE parameters of Bi2 Te3 /PEDOT:PSS composite thin films, through which enhanced TE performance is achieved. The findings demonstrate that proton irradiation of Bi2 Te3 is an effective method to engineer the TE properties through inducing defects in Bi2 Te3 and enhancing the interaction between Bi2 Te3 and PEDOT:PSS. Abstract : An enhancement in thermoelectric parameters is achieved through proton irradiation induced defects in flexible Bi2 Te3 /poly(3, 4‐ethylenedioxythiophene) doped with poly(styrene sulfonate) inorganic–organic composite thin films. The irradiation induced antisite defects are found beneficial in decoupling the interdependent thermoelectric parameters and achieving a high figure of merit.